A machine learning decision support tool optimizes WGS utilization in a neonatal intensive care unit - Edwin F. Juarez; Bennet Peterson; Erica Sanford Kobayashi; Sheldon Gilmer; Laura E. Tobin; Brandan Schultz; Jerica Lenberg; Jeanne Carroll; Shiyu Bai-Tong; Nathaly M. Sweeney; Curtis Beebe; Lawrence Stewart; et al. (npj Digital Medicine)
Abstract The Mendelian Phenotype Search Engine (MPSE), a clinical decision support tool using Natural Language Processing and Machine Learning, helped neonatologists expedite decisions to whole genome sequencing (WGS) to diagnose patients in the neonatal intensive care unit. After the MPSE was introduced, utilization of WGS increased, time to ordering WGS decreased, and WGS diagnostic yield increased.